2004
DOI: 10.1111/j.1532-950x.2004.04095.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Techniques for Supplementing Interlocking Nail Repair of Fractures of the Humerus, Femur, and Tibia: Results in 12 Dogs and Cats

Abstract: These 2 devices should be considered as alternative methods for stabilization of inadequately stabilized ILN repairs in dogs and cats, or when controlled destabilization of an ILN fracture repair is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 11 publications
4
33
1
Order By: Relevance
“…As previously reported clinically, and demonstrated in our study, dogs treated with a standard bolted ILN had gross torsional instability during the immediate and short term postoperative periods. In contrast, dogs treated with AS‐ILN in our study did not.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As previously reported clinically, and demonstrated in our study, dogs treated with a standard bolted ILN had gross torsional instability during the immediate and short term postoperative periods. In contrast, dogs treated with AS‐ILN in our study did not.…”
Section: Discussionsupporting
confidence: 86%
“…As locked implants that can be inserted from remote portals, ILNs have theoretical advantages including provision of adequate construct stability along with minimal disturbance of the fracture site, both of which may contribute to faster bone healing . Despite overall favorable clinical outcomes in human and veterinary medicine, including in cases of surgical revision, the reliability of conventional ILN designs in assuring fracture repair stability has been challenged . Indeed, acute construct instability, also referred to as slack, has been clinically documented and potentially could lead to inter‐fragmentary motion and subsequently delayed bone healing …”
mentioning
confidence: 99%
“…A force of 1.4 Nm was determined to create a rigid locking between the IM nail and the locking screws (unpublished data). As with the hourglass‐shaped ILN, this rigid locking mechanism is another advantage of the TVS over the current ILN systems, which lack a rigid locking mechanism and allow slack to occur . After modification of the torque wrench, no further slippage of the IM nail through the locking screws was observed.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, there is a mismatch of the locking devices with the hole in the intramedullary (IM) nail in most current ILN systems, causing slack. The latter is defined as the lack of rigid interaction between the locking devices (screws and bolts) and the nail resulting in acute and uncontrolled construct motion . Recently, an hour glass‐shaped ILN was introduced that offers a novel locking mechanism between the nail and the screw‐cone pegs .…”
mentioning
confidence: 99%
“…However, with the increased use of ILNs, the mechanical stability of fractures repaired with currently available ILN systems has recently been questioned in both the human and veterinary surgical literature 9–14 . Whereas veterinary clinical reports have described the use of various additional fixation to overcome perioperative instability in up to 12% of diaphyseal fractures treated with standard ILNs, 2,15–17 experimental investigations have suggested that such instability stems from an inherent deficiency in the locking mechanism. The lack of rigid interaction between the locking devices (screws or bolts) and the nail inevitably results in acute and uncontrolled construct motion (slack) 9,11,18 .…”
Section: Introductionmentioning
confidence: 99%